2019
DOI: 10.2217/fmb-2018-0260
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Evolutionary Features of type VI Secretion Systems in Salmonella

Abstract: Aim: Type VI secretion systems (T6SS) play key roles in bacterial pathogenesis, but their evolutionary features remain largely unclear. In this study, we conducted systematic comparisons among the documented T6SSs in Salmonella and determined their structural diversity, phylogenetic distribution and lineage-specific properties. Materials & methods: We screened 295 Salmonella genomes for 13 T6SS core components by hidden Markov models and identified 363 T6SS clusters covering types i1, i2, i3 and i4a. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In Salmonella enterica, T6SS gene clusters are encoded within different pathogenicity islands (SPIs), depending on the subspecies and serovar (Blondel et al, 2009;Bao et al, 2019). S. enterica subsp.…”
Section: Introductionmentioning
confidence: 99%
“…In Salmonella enterica, T6SS gene clusters are encoded within different pathogenicity islands (SPIs), depending on the subspecies and serovar (Blondel et al, 2009;Bao et al, 2019). S. enterica subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Typhimurium, 26 more similar to SPI-19 of S. enterica subsp. salamae ST114 (an in silico analysis), 38 thereby a new SPI-19 type found in Salmonella . The antibacterial activity assay revealed that S .…”
Section: Discussionmentioning
confidence: 99%
“…T6SSs are widespread among Salmonella spp. and are encoded in different SPIs (SPI-6, SPI-19, SPI-20, SPI-21, SPI-22) [194,195]. Only two SPI-6 T6SS antibacterial effectors have been characterized to date: Tae4 (type VI amidase effector 4) and Tlde1 (type VI L,D-transpeptidase effector 1), both effectors target the peptidoglycan of competitors by different mechanisms [196,197].…”
Section: Class I Microcins Include Mccb17 [162] Mccc7-c51 [163] and M...mentioning
confidence: 99%